Chemical and immunological characterizations of equine infectious anemia virus gag-encoded proteins. - Henderson, L E (1987)
The viral core proteins (p15, p26, p11, and p9) of equine infectious anemia virus (EIAV) (Wyoming strain) were purified by reverse-phase high-pressure liquid chromatography. Each purified protein was analyzed for amino acid content, N-terminal amino acid sequence, C-terminal amino acid sequence, and phosphoamino acid content. The results of N- and C-terminal amino acid sequence analysis of each gag protein, taken together with the nucleotide sequence of the EIAV gag gene (R. M. Stephens, J. W. Casey, and N. R. Rice, Science 231:589-594, 1986), show that the order of the proteins in the precursor is p15-p26-*-p11-p9, where a pentapeptide also found in the virus is represented by the asterisk. The data are in complete agreement with the predicted structure of the gag polyprotein and show the peptide bonds cleaved during proteolytic processing. The N-terminus of p15 is blocked to Edman degradation. The p11 protein is identical to the nucleic acid-binding protein of EIAV previously isolated (C. W. Long, L. E. Henderson, and S. Oroszlan, Virology 104:491-496, 1980). High-titer rabbit antiserum was prepared against each purified protein. These antisera were used to detect the putative gag precursor (Pr55gag) and intermediate cleavage products designated Pr49 (p15-p26-*-p11), Pr40 (p15-p26), and Pr35 (p26-*-p11) in the virus and in virus-infected cells. High-titer antisera to EIAV p15 and p26 showed cross-reactivity with the homologous protein of human T-cell lymphotropic virus type III/lymphadenopathy-associated virus.